2019
DOI: 10.3390/ijms20030597
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Hepatitis B Virus Mutations Leading to Endoplasmic Reticulum Stress and Their Contribution to the Progression of Hepatocellular Carcinoma

Abstract: Hepatitis B virus (HBV) infection is a global health problem that causes a wide range of pathological outcomes, including cirrhosis and hepatocellular carcinoma (HCC). Endoplasmic reticulum (ER) stress induction by HBV infection has been implicated in liver carcinogenesis and disease progression with chronic inflammation via enhanced inflammation, oxidative stress-mediated DNA damage, and hepatocyte proliferation. In the natural course of HBV infection, the accumulation of naturally occurring mutations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 84 publications
(106 reference statements)
2
48
1
Order By: Relevance
“…HBV mutations might affect the success rates of diagnostic/vaccination protocols, leading to the development of drug-resistant strains [33][34][35][36][37][38][39]. The expression, distribution, and secretion of HBV proteins could be affected by amino acid mutations that are also correlated with HCC [40][41][42][43]. Here, we identified an HBV strain from an acute clinically infected patient and performed full genome sequencing, characterization, mutational analysis, cloning, and expression analysis of the major viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…HBV mutations might affect the success rates of diagnostic/vaccination protocols, leading to the development of drug-resistant strains [33][34][35][36][37][38][39]. The expression, distribution, and secretion of HBV proteins could be affected by amino acid mutations that are also correlated with HCC [40][41][42][43]. Here, we identified an HBV strain from an acute clinically infected patient and performed full genome sequencing, characterization, mutational analysis, cloning, and expression analysis of the major viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The genes involved in the organelle membrane are all existed on the endoplasmic membrane. The relationship between the endoplasmic membrane and carcinogenesis of HCC may be involved in the ER stress (49), and more studies with high credibility are in need to validate this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Host cell-mediated N-glycosylation on L, but not on M or SHBs proteins is vital for viral morphogenesis [ 40 ]. Moreover, recent studies have shown that the N-glycans on LHBs are associated with ER stress-mediated cell cycle dysregulation and cell proliferation, triggering carcinogenic processes [ 41 , 42 ]. These findings clearly demonstrate that posttranslational modifications of LHBs play significant roles in regulating HBV carcinogenesis.…”
Section: Glycosylations Of the Lhbs Pre-s Regions That Regulate Prmentioning
confidence: 99%